THE IMPORTANCE OF CULTURE IN ORDER TO MAKE A GOOD ADVERTISEMENT IN TRANSLATION (Foreignizing and domestication in product advertisement) - Amminiyani Amminiyani (Universitas Negeri Medan, 2019)
This research deals with the importance of culture in translation to make a good language of advertisement. Its objective in language of advertisement that has no role in makes an advertisement. The result of this research is knowledge of the advertiser still low and limited understanding to make the language in advertisement. This research has a functional to another advertiser that want to make a good advertisement in foreign language certainly.Key words: importance, advertisement, culture in translation,